A large-bore chiral cylindrical molecule prone to radial deformations. (27th April 2022) - Onaka, Yuzuka; Tanaka, Shun; Kobayashi, Ayano; Matsuno, Taisuke; Isobe, Hiroyuki
Graphical abstract: Abstract: Theoretical screenings of D 4 -molecular cylinders for high- g chiroptical molecules were performed to find one four-panel cycloarylene with an anomalously high theoretical | g abs, calc | value of 1.97. Optical resolutions of enantiomers after developments of elaborate syntheses allowed for spectral analyses of the chiral D 4 -cylinder. Unexpectedly, the experimental | g abs | value was three orders of magnitude less than the theoretical prediction, and crystallographic analyses combined with theoretical investigations showed radial deformations as one of the possible factors that could considerably affect the | g | value.